A qualitative study on facilitators and barriers to adoption and implementation of nutrition interventions in higher education settings in Flanders - Evelyn Fonderie; Wendy Van Lippevelde; Benedicte Deforche; Maïté Verloigne; Lotte Braeckman; Jolien Plaete; Tom Deliens (Scientific Reports)
Abstract The transition from secondary school to college or university is a well-known and well-studied risk period for weight and/or fat gain and not meeting the dietary recommendations. Higher education acts as a promising setting to implement nutrition interventions. An important condition for intervention success is that interventions are implemented as intended by the protocol and integrated in the institutional policy. Unfortunately, to date, there is only little understanding of the factors influencing adoption and implementation of nutrition interventions in higher education settings. This study aimed to provide insight into stakeholders’ perspectives on facilitators and barriers to adoption and implementation of nutrition interventions promoting healthy and sustainable diets among higher education students in Flanders. Eight online group interviews and three online individual interviews were conducted involving a total of 37 stakeholders (e.g., staff of student services and student restaurants) from ten Flemish higher education institutions with varying food policy quality scores, and one external catering company which provides catering in higher education institutions. A semi-structured interview guide based on the Consolidated Framework for Implementation Research (CFIR-framework) was used to facilitate the interviews. Afterwards, the data were analyzed using a combined inductive and deductive thematic approach led by the CFIR-framework. Most of the institutions’ food policies focused on the provision and promotion of healthy and sustainable nutrition. Therefore, the reported factors in the present study consequently relate primarily to these two strategies. Stakeholders preferred to adopt low cost and institution-tailored interventions supported by experts and evidence, considering them easier and less resourceful to implement in the specific context of the institution. They stressed the importance of considering both students’ and institution stakeholders’ needs and perspectives in the development of nutrition interventions and implementation plans. Furthermore, interventions should be focused on a combination of different ecological levels and various strategies. Future interventions should be developed participatively and should be focused on a combination of both individual and environmental levels. Higher education institutions are encouraged to use opportunities such as creating win–win situations within the institution, working together with research groups and engaging students through student associations. The findings of this research add to the literature on implementation science and inform future development and implementation of nutrition interventions in higher education settings.